The last secret of the temple - Sussman, Paul (London Bantam Books, 2006)
Joining forces with Israeli cop Arieh Ben-Roi, Egyptian detective Yusuf Khalifa investigates the discovery of a body at an isolated archaeological site, a death he connects with a murdered Israeli, which ultimately leads to an enigma dating back to 70 A.D.
Keywords: Archaeologists -- Fiction; Excavations (Archaeology) -- Fiction; Murder -- Investigation -- Fiction; Police -- Egypt -- Fiction; Egypt -- Antiquities -- Fiction